Competency-Based Education in Multicultural Classrooms: Designing Culturally Responsive Teaching Strategies - Adrianus Prihartanto; Shirley A Padua; Alvin S Sicat; Rosmerry Simanjuntak; Henny Sutrisman (Journal Emerging Technologies in Education, 2025)
Background. Culturally diverse classrooms are increasingly the norm in many education systems worldwide, presenting both opportunities and challenges for equitable teaching and learning. Competency-Based Education (CBE), which emphasizes mastery of skills over time spent in instruction, holds significant promise in addressing student diversity. Purpose. However, without culturally responsive strategies, CBE may fall short in meeting the learning needs of students from varied cultural and linguistic backgrounds. Method. Using a qualitative multiple case study design, data were collected from nine teachers across three urban schools through interviews, classroom observations, and instructional material analysis. Results. These practices increased learner motivation, inclusivity, and performance. The findings highlight that aligning CBE with culturally responsive teaching enhances its applicability and equity in diverse classrooms. Conclusion. The study concludes that aligning CBE with culturally responsive teaching enhances its effectiveness in multicultural settings. It recommends embedding cultural relevance as a core component in CBE-based teacher training and curriculum development.